Kwalifikowanie umów zawieranych w obrocie na rynkach rolnych - Pytlak, Przemysław (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostęne wyłącznie w języku angielskim: One of the most important instruments utilsed by the European Union to influence the trade on the agricultural commodity markets are regulations concerning contracts between producers and undertakings operating on the markets. The EU’s regulations define contracts organising particular agricultural markets (i.e. hops, tobacco, sugar, milk markets) through dermining demands whitch those contracts should fulfill without creating named contracts, incorporated to law systems of the member countries. The present study proposes how to qualify contracts regulated by european law on the basis of polish law system. The principle of the proposed qualification is comparison between obligations resulting from contracts regulated by european law and obligation scheme resulting from the definition of one the named contracts described by civil code.